New Complexes of Co(II) With Benzilbis (semicarbazone) & Amino Acids - Zuhoor Dawood; Rawa Sulman (College of Education for Pure Sciences, 2008)
ABSTRACT New cobalt (II) complexes with mixed ligands including benzilbis(semi- carbazone)-BscH2 and amino acids-AH {glycine (GlyH) or alanine (AlaH) or cysteine (CysH) or cystine (CyH) or tyrosine (TyrH) or histidine (HisH) or threonine (ThrH) or proline (ProH)} have been prepared and characterized physiccochemically. They have been found to have general formulas [Co(BscH2)(AH)(NO3)](NO3) or [Co(BscH2)(AH)](NO3)2 and [Co(BscH)(A)] in neutral and basic medium, respectively (where AH = any of the amino acid, A = deprotonated amino acid, BscH = deprotonated BscH2 ligand). The results supported that the complexes had high spin octahedral geometries.